Reuse of glass in concrete: a study of the production and mechanical performance of resistance - Paz, Lidiane Andrade Fonseca da; Santos, Vando Dias dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The glass incorporated into the concrete contributes to the conservation of the environment, as it will have a correct destination and is an easily found material. This work had the objective of analyzing the mechanical performance of the concrete produced with glass waste from non-returnable packaging. Since glass is a residue that is easily found, it is justified to incorporate it into concrete in partial replacement of small aggregates, thus avoiding its disposal in landfills and also in an irregular way. The concrete produced was made with the addition of “51” and “Long Neck” ground glass. A standard trace of 25 MPa was defined, with partial substitutions of 5%, 15%, 25% and 35% in the small aggregate. The individual strengths of the test specimens were submitted to the Tukey test for statistical analysis and it was verified that the trait with the percentage of 35% substitution is statistically different from the other traits. The concrete had a mean Fck of 32,37 MPa, higher than the established minimum of 25 MPa. It can be concluded that the concrete with the use of ground glass presents technical feasibility for execution and contributes to the preservation of the environment.